2020
DOI: 10.1063/1.5124802
|View full text |Cite
|
Sign up to set email alerts
|

Role of host excimer formation in the degradation of organic light-emitting devices

Abstract: Host-guest structures are used in most state-of-the-art organic light-emitting devices, with the host transporting charge and confining excitons on the guest. While the host often plays a critical role in achieving high efficiency and stability, predicting and understanding these effects is a persistent design challenge which slows the discovery of new active materials. Closely related host molecules, which differ only by several functional groups, often show drastically different degradation behavior. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Newcomb et al has identified the necessity to screen potential TADF OLED emitters for exciplex formation, as the presence of exciplexes was shown to lower device lifetime. 119 Masui et al also identified large EQE roll-off in OLEDs caused by charge imbalance in the emissive layer that are exacerbated at higher current densities. 109,120 The exciplex formation in these compounds is characteristic of compounds that also exhibit OLPL, thereby supporting OLECL emission as the dominant mechanism.…”
Section: Ecl Spectroscopymentioning
confidence: 99%
“…Newcomb et al has identified the necessity to screen potential TADF OLED emitters for exciplex formation, as the presence of exciplexes was shown to lower device lifetime. 119 Masui et al also identified large EQE roll-off in OLEDs caused by charge imbalance in the emissive layer that are exacerbated at higher current densities. 109,120 The exciplex formation in these compounds is characteristic of compounds that also exhibit OLPL, thereby supporting OLECL emission as the dominant mechanism.…”
Section: Ecl Spectroscopymentioning
confidence: 99%
“…As the device was under operation, the EL intensity showed a gradual decrease with no change in the spectral shape (Figure 2a), suggesting no new emissive materials forming in the EML and no significant shift of the recombination zone, which implies that the out-coupling efficiency of the device remains unchanged during operation. 25,26 The T50 (time that the EL intensity drops to 50% of its initial intensity) of the device was 2715 h, as determined by fitting the EL intensity drop to a stretched exponential decay function (Figure S1c). No dark spots were formed during operation, which means that external degradation factors such as particles introduced in the device fabrication process or electrode oxidation can be excluded.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Newcomb et al has identified the necessity to screen potential TADF OLED emitters for exciplex formation, as the presence of exciplexes was shown to lower device lifetime. 112 Masui et al also identified large EQE roll-off in OLEDs caused by charge imbalance in the emissive layer that are exacerbated at higher current densities. 101,113 The exciplex formation in these compounds is characteristic of compounds that also exhibit OLPL, thereby supporting OLECL emission as the dominant mechanism.…”
Section: Ecl Spectroscopymentioning
confidence: 99%